Interspecific competition between restocked 0+ salmon parr (Salmo salar) and native fish species in a large European river. Issue 1 (13th July 2018) - Floury, Mathieu; Colombet, Jonathan; Desvilettes, Christian
Abstract: Atlantic salmon populations have experienced strong declines in most large European rivers. In the Loire Basin, France, a major restocking effort has been carried out on the Allier River to reduce the wild population decline. This study aimed at investigating the trophic insertion of hatchery‐reared salmon parr and whether they compete for resources with native fish species. For this purpose, two riffles located in the upstream and downstream parts of the restocked area have been surveyed monthly following the initial 0+ salmon fry release. 0+ parr densities remained high upstream, with autumnal values greater than those recommended to maximise smolt production. In contrast, downstream densities declined to weak values despite a faster increase in size, probably mainly due to summer temperatures rising above the discomfort threshold. By analysing the vulnerability to predation of ingested invertebrate prey, we highlighted the role of habitat constraints in driving most of the different fish species to a likely opportunistic utilisation of available food resources. As a result, species such as stone loaches and barbel juveniles exhibited narrow trophic niches and high overlaps with 0+ parr. Nonetheless, both abundant prey resources and spatial or temporal habitat segregation have limited interspecific competition, enabling competitive coexistence of sympatric species, except for barbel juveniles in certain circumstances. Therefore, our findings suggest that future restocking programmes should carefully consider the thermal and hydraulic conditions regarding further smolt production as well as their general trophic context, according to the potential inconvenience of restocked salmon fry arrival relative to native species.